Rationalizing rules for immunotherapy combination trials: About time for precision immunotherapy. Issue 1 (30th October 2022) - Desai, Aakash; Subbiah, Vivek
Lay summary: Immunotherapy has changed the landscape of cancer treatment. However, the benefit of immunotherapy is seen only in some cases, with most patients experiencing cancer progression despite treatment with immunotherapy. To overcome this, combination immunotherapy treatments are being studied. Herein, we propose for a precision‐driven approach for patient selection to identify successful combinations of immunotherapy to improve outcomes for patients with cancer. Abstract : Despite the success of immunotherapy, single‐agent immunotherapy fails to achieve durable disease control in most immune‐responsive tumors. Successful combinations and smartly designed studies would require improved patient selection for a much needed "precision immunotherapy" approach to identify the right dose of the right immunotherapy combination for the right patient at the right time.